2020
DOI: 10.1099/mgen.0.000435
|View full text |Cite
|
Sign up to set email alerts
|

Universal whole-sequence-based plasmid typing and its utility to prediction of host range and epidemiological surveillance

Abstract: Bacterial plasmids play a large role in allowing bacteria to adapt to changing environments and can pose a significant risk to human health if they confer virulence and antimicrobial resistance (AMR). Plasmids differ significantly in the taxonomic breadth of host bacteria in which they can successfully replicate, this is commonly referred to as ‘host range’ and is usually described in qualitative terms of ‘narrow’ or ‘broad’. Understanding the host range potential of plasmids is of great interest due to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(134 citation statements)
references
References 35 publications
0
119
0
Order By: Relevance
“…Another strength of our study was extensive use of long-and short-read sequencing to construct high-quality hybrid plasmid assemblies. Combining these techniques with non-alignment methods of determining sequence similarity creates a powerful tool for detecting spread of mobile genetic elements with important implications for infection prevention [32,33]. By doing this, we J o u r n a l P r e -p r o o f demonstrated that in our institution IncHI2 plasmids likely were transmitted by both clonal and interspecies spread.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Another strength of our study was extensive use of long-and short-read sequencing to construct high-quality hybrid plasmid assemblies. Combining these techniques with non-alignment methods of determining sequence similarity creates a powerful tool for detecting spread of mobile genetic elements with important implications for infection prevention [32,33]. By doing this, we J o u r n a l P r e -p r o o f demonstrated that in our institution IncHI2 plasmids likely were transmitted by both clonal and interspecies spread.…”
Section: Discussionmentioning
confidence: 82%
“…Finally, we used non-alignment-based approaches to cluster plasmid genomes but there are few current data which would help define similarity cutoffs to indicate plasmid transmission. Prior reports have assessed plasmid diversity within single J o u r n a l P r e -p r o o f patients [44] and outbreaks [45] but further data across diverse plasmids and host backgrounds are needed to inform infection prevention decisions [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we investigated a total of 18 plasmid incompatibility groups in all E. coli isolates. We were able to identify several isolates that carry IncN, P, HI1, and I1 incompatibility groups that have been shown to be associated with a broad-host range [ 76 , 77 , 78 ]. Interestingly, in our study, all ESBL-producing E. coli in the CC environment carried IncK/B type plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…We then tested another prediction of the cooperation hypothesis: cooperation is more likely to be favoured when coded for on more mobile plasmids [14][15][16][17][18] . We used data from the MOBsuite database to assign plasmids to one of three levels of mobility (Fig 3a) 44,45 . We classify: conjugative plasmids, which carry all genes necessary to transfer, as the most mobile; mobilizable plasmids, which are dependent upon conjugative plasmids' machinery to transfer, to have intermediate mobility; non-mobilizable plasmids, which cannot be transferred via conjugation, to be the least mobile (Fig 3a) 44,46 .…”
Section: Difference In Proportionmentioning
confidence: 99%